Effectiveness of injectable platelet-rich fibrin in conjunction with scaling and root planing as local drug delivery in the treatment of periodontitis - Vanaki, Bhagyashri N.; Kokatnur, Vijayalaxmi M.; Hugar, Shruti; Kalburgi, Nagaraj B.; Roy, Anjaly; Karwir, Aditi M. (International Journal Of Community Medicine And Public Health, 2025)
Periodontitis is a multifactorial disease, characterized by the progressive destruction of periodontal supporting tissues, resulting in periodontal pocket formation. Scaling and root planing (SRP) is not frequently resolute at repairing disease-related defects. To enhance the regeneration, adjunctive therapeutic procedures have been added to conventional therapy. Platelets are important reservoirs of various GFs and cytokines, which are vital in wound repair and homeostasis. Therefore, this study aimed to assess the effectiveness injectable formulation of platelet rich fibrin (I-PRF) enables easier use of the platelet concentrate in a liquid state. A total of 20 periodontitis subjects were selected and divided using a split-mouth study design into control site: SRP alone and test site: SRP + I-PRF injection. Clinical parameters like-gingival index (GI), plaque index (PI), bleeding on probing (BOP), clinical attachment loss (CAL), pocket probing depth (PPD) were evaluated at baseline and 6 weeks. Statistically significant reduction in the clinical parameters observed in both the sites. But comparatively, test site showed more reduction in clinical parameters with gain in CAL when compared to control site. I-PRF when used along with SRP show therapeutic benefit in periodontal regeneration.